The golden rule of public finance and the productivity of public capital - Terezie Výprachtická (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This paper concentrates on the golden rule of public finance. It reviews the main advantages and disadvantages of the potential implementation of this rule in the European Union. Often the question of the productivity of public capital is at the heart of the rule's discussions. As this issue has mostly been investigated for the United States, we try to estimate the productivity of public capital using data on the current member states of the European Union. Working both with data on net capital stocks and gross capital formation, we come to the conclusion that there is a cointegrating relationship between capital and output and that this relationship is in most cases positive. However, as there are also other expenditures classified as current spending that have a positive effect on the output in the long run, we argue that the golden rule should not be introduced in the European Union if the current definition of public capital investment does not change for the rule's purposes.
Keywords: C23; E22; E62; H52; H62; 330; Golden rule of public finance; European Union; Cointegration; Productivity of capital; Cobb-Douglas production function; Öffentliche Ausgaben; Öffentliche Investition; Finanzpolitik; Regelbindung; Kapitalproduktivität; Kointegration; EU-Staaten